Understanding water institutions: structure, environment, and change process - Saleth, Rathinasamy Maria (2004)
Water institutions are critical for enhancing the development impact of water resource management. But, considerable ambiguity and divergence persists as to the way they are to be approached and evaluated causing serious conceptual and policy distortions. Utilizing some recent developments in the literature on the subject, this paper presents a simple but generalizable framework for understanding, explaining, and evaluating water institutions and their change process. It uses an analytical decomposition of water institutions to show their endogenous and exogenous linkages, transaction cost approach to conceptually account for the role of various factors, and a stage-based perspective to shed light on the internal mechanics and dynamics evident in the process of water institutional change. Despite its analytical and theoretical orientation, the paper does have some major implications for the practical and policy dimensions of water institutional reforms. It indicates how the institutional design and implementation principles derived from the structure and context of water institutions can be used to promote reforms and demonstrates how a better understanding of the change process can lead to strategies for setting the overall reform climate, especially through public education, reform research, and institutional supply